Purposes of Evaluation of University Instructors: Definitions, Delineations and Dimensions - Glasman, Naftaly S.; Gmelch, Walter H. (Canadian Journal of Higher Education, 1976)
Research and writings on evaluation of college and university instructors are expanding. Not unrelated to this phenomenon are controversies which focus on justification and use of ratings of instructors1 as well as attempts to meet demands and ward off pressures for ac- countability. Also not unrelated to it are uncertainties and confusion surrounding purposes of evaluation of instructors and a widespread feeling that no single evaluation instrument can best suit more than one purpose. This paper describes considerations for establishing purposes of evaluation. We discuss definitions, delineations, and dimensions of purposes, and propose general models which can serve as guidelines for further development and specification of purposes.